A new species of the genus Meganola Dyar, 1898 (Lepidoptera, Nolidae, Nolinae) from China - Han, Huilin; Hu, Yanqing (Zootaxa, 2016)
Meganola is a large and morphologically rather diverse genus, which is widely distributed on all continents, although it proved to be the most species rich in the mountains of Southeast Asia. In this article, the new species Meganola tibetensis was collected at Tibet and reminds externally Himalayan-Indochinese species Meganola mediofusca László, Ronkay & Witt, 2007. These two species have similar configuration of female genitalia concerning the spinulose signum, but their male genitalia are totally different. In male genitalia, harpe approximate trapezoid and aedeagus without cornuti in new species, while in M. mediofusca harpe claw-like and aedeagus armed with many spines. Adults and genitalia of both species are illustrated.